Effect of intrauterine infection on brain development and injury. Issue 7 (3rd July 2013) - Zhao, Jing; Chen, Yurong; Xu, Yuxia; Pi, Guanghuan
Abstract: Intrauterine exposure of term and premature infants to infection/inflammation may increase the risk of perinatal brain injury, which may be more serious than that incurred by interpartum exposure to hypoxia–ischemia (HI). Many microorganisms, including certain viruses, protozoa, and bacteria, have been linked to this injury. In regard to the mechanisms of intrauterine infection‐triggered brain injury, the inflammatory risk factors such as cytokines play a central role. The inflammation signal is likely transmitted across the blood–brain barrier and initiates a neuroinflammatory response. Studies have reported that polymorphism of cytokine genes also has been implicated in perinatal brain injury. Moreover, inflammation and HI may be synergistically involved in this process. Although the relationship between inflammation and adverse neurodevelopmental outcome in affected infants is slowly being elucidated, the literature contains scant evidence of measures that can improve fetal neurologic outcome. Several pharmacologic molecules such as magnesium sulphate, erythropoietin, and corticosteroids as a neuroprotective agent for the fetus need further investigation.